Extraction of microalgal lipids and the influence of polar lipids on biodiesel production by lipase-catalyzed transesterification. (September 2016) - Navarro López, Elvira; Robles Medina, Alfonso; González Moreno, Pedro Antonio; Esteban Cerdán, Luis; Molina Grima, Emilio
Highlights: Lipids were extracted from wet microalgal biomass by using seven extraction systems. Lipid fractions with polar lipid contents between 75.1% and 15.3% were obtained. An extracellular lipase and an intracellular lipase were used as catalysts. Lipase catalyzed methanolysis velocity is higher the lower the polar lipid content. Lipase stability is lower as higher was the polar lipid content. Abstract: In order to obtain microalgal saponifiable lipids (SLs) fractions containing different polar lipid (glycolipids and phospholipids) contents, SLs were extracted from wet Nannochloropsis gaditana microalgal biomass using seven extraction systems, and the polar lipid contents of some fractions were reduced by low temperature acetone crystallization. We observed that the polar lipid content in the extracted lipids depended on the polarity of the first solvent used in the extraction system. Lipid fractions with polar lipid contents between 75.1% and 15.3% were obtained. Some of these fractions were transformed into fatty acid methyl esters (FAMEs, biodiesel) by methanolysis, catalyzed by the lipases Novozym 435 and Rhizopus oryzae in tert-butanol medium. We observed that the reaction velocity was higher the lower the polar lipid content, and that the final FAME conversions achieved after using the same lipase batch to catalyze consecutive reactions decreased in relation to an increase in the polar lipid content.